KAJIAN LIVING LAW TERHADAP MAHAR BHOKA DALAM PERNIKAHAN BEDA STRATA SOSIAL SUKU BUTON : Prespektif Hukum Islam - Rismayani; Muhammad Andi Akmal; St. Halimang, , St. Halimang,; Pabbabari, Musafir; Said, Irwanti (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
This study examines the tradition of determining the bhoka dowry in inter-social strata marriages within the Buton Tribe in Baubau City. In Buton’s customary law, society is divided into three social classes: Kaomu (nobility), Walaka (middle class), and Papara (commoners), each with different dowry values regulated by the Sultanate. Traditionally, marriages between Kaomu women and Papara men are prohibited and subject to customary fines. Using a descriptive qualitative method with an Islamic legal sociology approach—applying the theories of Living Law, Symbolic Interactionism, and ‘Urf—this research involved interviews with traditional, religious, and community leaders, as well as inter-class married couples, through snowball sampling, alongside observation and documentation. The findings reveal three main stages in determining the dowry: lukuti, pesoloi, and losa, which include a lineage tracing process (tiliki) by a spokesperson (tolowea) to decide dowry amounts and customary sanctions for inter-class unions. Community leaders’ perspectives on inter-social marriages are divided, though most view the traditional prohibitions as no longer relevant amid modern social dynamics. Furthermore, the dowry custom in inter-social marriages still functions as a living law within the Buton community, as it meets the core principles of the Living Law theory.